Palliative medicine Master Classes for primary care: an evaluation - Persijn J. Honkoop; Raewyn Jenkins; Amanda Landers (CSIRO Publishing, 2022)
Introduction General practitioners (GP) are key in the delivery of primary palliative care in the community, so appropriate knowledge and skills are needed. Previous research has suggested there may be gaps in training opportunities. Aims To develop and evaluate a Master Class series presented by a hospice palliative care service to their local GPs and other health-care professionals. A secondary aim was to measure the lasting impacts of the educational intervention. Methods The study setting was the Canterbury region of Aotearoa New Zealand (NZ). GPs and other health-care professionals were surveyed using a research team-designed questionnaire rating self confidence in the nominated learning objectives before and after the Master Classes. The participants were also asked to self-rate the application of the knowledge to their practice 3 years after the Master Class sessions were attended. Results There were 56 sets of questionnaires completed. The participants tended to be experienced female GPs with a range of palliative care patients in their practice. There was significant improvement in most learning outcomes across the Master Classes series. The attendees reported the Master Classes were relevant and clear, with useful resources. The improvements in the learning outcomes were largely sustained over 3 years. Discussion The provision of palliative care education that aligns with clinical practice improves knowledge, skills and confidence in GPs who provide most of the end-of-life care in New Zealand.